IT Security Risk Control Management An Audit Preparation Plan - Pompon, Raymond (Apress : Imprint: Apress, 2016)
Information security is more than configuring firewalls, removing viruses, hacking machines, or setting passwords. Creating and promoting a successful security program requires skills in organizational consulting, diplomacy, change management, risk analysis, and out-of-the-box thinking. IT Security Risk Control Management provides step-by-step guidance for IT professionals on how to craft a successful security program. Readers will identify with the paradoxes of information security and discover handy tools that hook security controls into business processes, including: Building a security program that will fit neatly into an organization and change dynamically to suit both the needs of the organization and survive constant changing threats Preparing for and passing such common audits as PCI-DSS, SSAE-16, and ISO 27001. Calibrating the scope, and customizing security controls to fit into an organization's culture. Implementing the most challenging processes, pointing out common pitfalls and distractions. Framing security and risk issues to be clear and actionable so that decision makers, technical personnel, and users will listen and value your advice. With IT Security Risk Control Management, you will be able to construct an information security program, from inception to audit, with enduring, practical, hands-on advice, and actionable strategies for IT professionals.